INFLUENCE OF MICELLAR CATALYSIS ON THE STRENGTH OF ALKALINE REACTIVE POWDER CONCRET - Шишкіна, Олександра (SWorldJournal, 2025)
It has been shown that under certain conditions, an increase in the rate of hydration of the binder helps to increase the compressive strength of concrete. This is especially true for reactive powdered concretes. Taking into account the specific effect of